Simulasi keselamatan dan kesehatan kerja (K3) pekerja PT. Tukang Bangun Indonesia - Harjanto, Furqaan; Shidiq, Muhammad Ghofar; Yunianto, Ardian (Jurnal PADE: Pengabdian & Edukasi, 2024)
Work accidents occur due to several things, namely weak supervision on the project, undisciplined labor in complying with OHS, and inadequate personal protective equipment on the project in terms of quantity and quality. The problem may occur to workers of PT. The method used is by counseling workers from PT.Tukang Bangun Indonesia which was held on Saturday, June 08, 2024 at the PT.Tukang Bangun Indonesia office, Surakarta with a total of 11 participants and participants consisted of office workers and field workers with a more dominant proportion of field workers, this is because field workers have a greater potential for work accidents. The counseling was conducted with lectures and presentations conducted collaboratively by students and lecturers. The pre-test was conducted to determine the participants' initial understanding, then a post-test was conducted to measure the increase in participants' understanding when compared to the pre-test results. Based on the results of the pre-test and post-test evaluations, it was found that only 49.8% of participants understood about OHS, and the results of understanding after the workshop increased to an average of 88.5% of participants understood about OHS, so based on the results of the evaluation, it can be concluded that the workshop conducted has been able and effective to improve the ability and understanding of participants from PT. Tukang Bangun Indonesia workers related to Occupational Safety and Health (K3)